Workshop Publikasi Artikel ke Jurnal Terakreditasi - Ruqiah Ganda Putri Panjaitan; Yuliati Indrayani; Kiki Prio Utomo; Ayong Hiendro; Muhammad irfani Hendri; Intan Putri; Alya Zatira (Jurnal Pengabdian Kepada Masyarakat, 2026)
The publication of scientific articles is an important indicator in developing teacher professionalism. However, teachers' abilities in publishing scientific articles are still relatively low. This activity aims to provide teachers with an understanding of writing and the procedures for publishing scientific articles in accredited journals. The methods used are face-to-face presentations and discussions. The subjects of this community service activity are teachers at SDN 24 Pontianak Tenggara. The instrument used is a post-test questionnaire. The post-test results indicate an improvement in teachers' understanding of scientific article writing and publication. A challenge in the workshop was the limited time available for completing the articles, so further guidance is needed in the process of submitting articles to the OJS system.